Bio-inspired nanocomposite coatings on orthodontic archwires with corrosion resistant and antibacterial properties - Chen, Yuming; Chen, Zihan; Zheng, Zebin; Xia, Yong (Frontiers in Bioengineering and Biotechnology, 2023)
The corrosion resistance and antibacterial properties of fixed orthodontic devices are insufficient in the complex oral cavity, which delays tooth movement and causes tooth demineralization. To overcome the challenges, this research constructs a series of polydopamine-graphene oxide (PDA-GO) nanocoatings on representative NiTi archwires via self-assembly. The morphology, chemical structure, and multifunctional properties of coatings showed tunability dependent on the PDA/GO ratio. Optimized PDA-GO coatings with uniform and dense characteristics prolonged the diffusion path for the corrosive medium and reduced Ni dissolution in NiTi alloys. Meanwhile, the applied coatings endowed NiTi alloys with antibacterial activity against Streptococcus mutans due to the surface structures and inherent properties of PDA-GO. In vitro cytotoxicity tests further verified their good biocompatibility. This bio-inspired nanocomposite coating provides a practical reference for modification of dental metal surfaces to better behave in the intraoral environment.